A method for improving the inclusion capacity of CeO2 in borosilicate glass cured body
Patent Information
- Application Number
- CN202410719289.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-05
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-06-05
AI Technical Summary
但是传统硼硅酸盐对CeO2的包容量较低(≤10wt%),例如“Crystallization behavior,quantitation of Ce3+/Ce4+and chemical stabilityanalysis ofmultiple alkaline earths borosilicate glasses for immobilizingsimulated tetravalent actinides[J].”(Yu H,Xin R,Zhang X,et al.Journal ofNon-Crystalline Solids,2021,558(22):120642.)公开了采用高温熔融冷却得到玻璃固化体样品,对CeO2的最大包容量为10wt%
[0021] Furthermore, the method provided by this invention only requires the direct introduction of La2O3, which is both a component of high-level radioactive waste liquid and can serve as an actinide analog nuclide, into the raw material mixing process. It eliminates the need for stirring and mixing during the melting process and for secondary heat treatment. Therefore, the method provided by this invention is simple, easy to implement, and suitable for widespread application.
Smart Images

Figure CN118479728B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high-level radioactive waste liquid vitrification technology, specifically relating to a method for increasing the inclusion capacity of CeO2 in borosilicate glass curing bodies. Background Technology
[0002] High-level radioactive waste (HDW) refers to liquid HDW and its solidified forms generated from the reprocessing of spent fuel in the nuclear fuel cycle, as well as spent fuel intended for direct disposal. It is characterized by high specific activity, high heat release rate, and the presence of nuclides with long half-lives and high biotoxicity. Therefore, its treatment and disposal technologies are complex, difficult, and costly, making it a key research and development area in radioactive waste management. The most reasonable approach to radioactive waste disposal is considered to be first solidifying the waste, followed by final geological disposal of the solidified form. Nuclear vitrification involves mixing nuclear waste with glass additives, melting the mixture at high temperatures, and casting it into a vitrified body. Radioactive elements are solidified within the glass at the atomic scale, ensuring the safety of its geological storage.
[0003] CeO2 is a major analogue of trivalent and tetravalent actinide nuclides, and it is also a component of high-level radioactive waste. Therefore, studying the CeO2 encapsulation capacity of borosilicate glass is of great significance for the curing of high-level radioactive waste using borosilicate glass. However, traditional borosilicates have a low CeO2 encapsulation capacity (≤10wt%), for example, in the study of "Crystallization behavior, quantitation of CeO2". 3+ / Ce 4+ and chemical stability analysis of multiple alkaline earths borosilicate glasses for immobilizing simulated tetravalent actinides[J]. (Yu H,Xin R,Zhang X,et al.Journal ofNon-Crystalline Solids,2021,558(22):120642.) disclosed a glass-solidified sample obtained by high-temperature melting and cooling, with a maximum CeO2 inclusion capacity of 10wt%.
[0004] However, such small package sizes are clearly insufficient for high-level radioactive waste liquids that have undergone vitrification. Summary of the Invention
[0005] The purpose of this invention is to provide a method for increasing the encapsulation capacity of CeO2 in borosilicate glass curing bodies. The method provided by this invention can not only effectively increase the encapsulation capacity of borosilicate for CeO2, but also achieve simultaneous curing of La2O3 in high-level radioactive waste liquid, and can also effectively improve the chemical stability of borosilicate glass curing bodies.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] This invention provides a method for improving the inclusion capacity of CeO2 in borosilicate glass cured bodies, comprising the following steps:
[0008] Borosilicate glass powder, CeO2, and La2O3 are mixed to obtain a mixture; the mass percentage of CeO2 in the mixture is >10%.
[0009] The mixture is melted to obtain a glass melt;
[0010] The glass melt is cooled to obtain a borosilicate glass solidified body.
[0011] Preferably, the mass percentage of La2O3 in the mixture is 0-6%, and not 0.
[0012] Preferably, the mass percentage of La2O3 in the mixture is 1-5%.
[0013] Preferably, the mass percentage of La2O3 in the mixture is 3-5%.
[0014] Preferably, the mass percentage of CeO2 in the mixture is 11-15%.
[0015] Preferably, the mixing includes grinding or ball milling, and the mixing time is 40 to 45 minutes.
[0016] Preferably, the holding temperature for melting is 1250–1300°C, and the holding time is 2–3 hours.
[0017] Preferably, the heating process from room temperature to the melting holding temperature includes: heating from room temperature to an intermediate temperature at a first heating rate, performing a pre-holding treatment at the intermediate temperature, and then heating from the intermediate temperature to the melting holding temperature at a second heating rate; the intermediate temperature is 800-850°C, and the pre-holding treatment time is 1-2 hours.
[0018] Preferably, the first heating rate and the second heating rate are independently 5 to 10 °C / min.
[0019] Preferably, after obtaining the glass melt and before cooling, the process further includes: casting the glass melt, wherein the mold used for casting is preheated.
[0020] This invention provides a method for increasing the inclusion capacity of CeO2 in borosilicate glass cured bodies, comprising the following steps: mixing borosilicate glass powder, CeO2, and La2O3 to obtain a mixture; wherein the mass percentage of CeO2 in the mixture is >10%; melting the mixture to obtain a glass melt; and cooling the glass melt to obtain a borosilicate glass cured body. This invention utilizes the characteristics of La2O3, which is a component of high-level radioactive waste and can also serve as an actinide analog nuclide, by adding La2O3 to basic borosilicate glass and CeO2 (a simulated nuclide). La2O3 acts as a glass network modifier, increasing the amount of NBOS (non-bridging oxygen) in the cured body, causing the glass network to depolymerize and increasing the inclusion capacity of borosilicate glass for CeO2, thereby obtaining a glass cured body with a larger CeO2 inclusion capacity. Simultaneously, the introduction of La2O3 into the borosilicate glass cured body also improves the chemical stability of the cured body. The results of the examples show that the normalized leaching rates of Ca and Si elements in the borosilicate glass cured body remained at 10% after 28 days. -4 g·m -2 ·d -1 Ce element consists of 10 -7 g·m -2 ·d -1 As the concentration of La2O3 increases, the leaching rate decreases to an undetectable level, and the leaching rate of La element cannot be measured by instruments, demonstrating excellent anti-leaching performance.
[0021] Furthermore, the method provided by this invention only requires the direct introduction of La2O3, which is both a component of high-level radioactive waste liquid and can serve as an actinide analog nuclide, into the raw material mixing process. It eliminates the need for stirring and mixing during the melting process and for secondary heat treatment. Therefore, the method provided by this invention is simple, easy to implement, and suitable for widespread application. Attached Figure Description
[0022] Figure 1 The XRD pattern of the borosilicate glass curing agent in this embodiment of the invention;
[0023] Figure 2 The image shown is a scanning electron microscope (SEM) image of a borosilicate glass cured sample from an embodiment of the present invention.
[0024] Figure 3 The above is an energy dispersive spectroscopy (EDS) spectrum of the borosilicate glass cured sample in an embodiment of the present invention. Detailed Implementation
[0025] This invention provides a method for improving the inclusion capacity of CeO2 in borosilicate glass cured bodies, comprising the following steps:
[0026] Borosilicate glass powder, CeO2, and La2O3 are mixed to obtain a mixture; the mass percentage of CeO2 in the mixture is >10%.
[0027] The mixture is melted to obtain a glass melt;
[0028] The glass melt is cooled to obtain a borosilicate glass solidified body.
[0029] In this invention, unless otherwise specified, all raw materials / components used in the preparation are commercially available products well known to those skilled in the art.
[0030] In this invention, the inclusion capacity of CeO2 in the borosilicate glass cured body is the mass percentage of CeO2 in the borosilicate glass cured body.
[0031] This invention involves mixing borosilicate glass powder, CeO2, and La2O3 to obtain a mixture; the mass percentage of CeO2 in the mixture is >10%. In this invention, the composition of the borosilicate glass powder is expressed in the form of oxides, and the preferred mass percentage of each oxide in the borosilicate glass powder is shown in Table 1.
[0032] Table 1 shows the composition of borosilicate glass powder in oxide form.
[0033] Mass fraction (wt%) 54.73 14.96 5.34 2.66 4.51 8.20 5.33 4.27
[0034] In this invention, the mass percentage of CeO2 in the mixture is preferably 10-20%, but not 10%, more preferably 10-15%, and not 10%, and even more preferably 11-15%. In a specific embodiment of this invention, the mass percentage of CeO2 in the mixture is specifically 15%.
[0035] In this invention, the mass percentage of La2O3 in the mixture is preferably 0-6%, but not 0, more preferably 1-5%, further preferably 3-5%, and specifically preferably 1%, 2%, 3%, 4%, 5% or 6%.
[0036] In this invention, the mixing preferably includes grinding or ball milling. The grinding is preferably carried out in an agate mortar. The ball milling is preferably carried out in a planetary ball mill. The mixing time is preferably 40–45 minutes. Specifically, the ball milling is preferably dry grinding.
[0037] After obtaining the mixture, the present invention melts the mixture to obtain a glass melt. In the present invention, the holding temperature for melting is preferably 1250–1300°C, specifically preferably 1300°C; the holding time is preferably 2–3 hours, more preferably 3 hours. The heating procedure from room temperature to the holding temperature for melting preferably includes: heating from room temperature to an intermediate temperature at a first heating rate, performing a pre-holding treatment at the intermediate temperature, and then heating from the intermediate temperature to the holding temperature for melting at a second heating rate. In the present invention, the intermediate temperature is preferably 800–850°C, and the pre-holding treatment time is preferably 1–2 hours. The first heating rate is preferably 5–10°C / min. The second heating rate is preferably 5–10°C / min.
[0038] After obtaining the glass melt, but before cooling, the present invention preferably further includes: casting the glass melt. The mold used for casting is preferably preheated. The preheating temperature for the mold preheating treatment is preferably 400–700°C. The present invention does not have specific requirements for the specific implementation of the preheating treatment.
[0039] After casting, the present invention cools the glass melt cast in the mold to obtain a borosilicate glass solidified body. The present invention does not have specific requirements for the specific implementation method of the cooling. Air cooling is preferred.
[0040] The method provided by this invention does not require stirring and mixing during the melting process, nor does it require secondary heat treatment.
[0041] To further illustrate the present invention, the technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0042] Example 1
[0043] Experimental studies have shown that the maximum CeO2 inclusion capacity of the basic borosilicate glass formulation used in this embodiment is 10 wt%. Any amount exceeding this capacity will precipitate as CeO2. However, if the amount of CeO2 added is too small, the precipitated CeO2 will not be detectable by XRD. Therefore, in this embodiment, the final CeO2 content in the cured borosilicate glass is selected to be 15 wt%.
[0044] The method for preparing the borosilicate glass cured body in this embodiment includes:
[0045] 1. With a total solidified sample weight of 30g, weigh CeO2 with a mass percentage of 15wt% using an analytical balance. Then weigh La2O3 with mass percentages of 0wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, and 6wt%, respectively. Finally, weigh the basic borosilicate glass powder.
[0046] The composition of the basic borosilicate glass powder used in this embodiment is shown in Table 2:
[0047] Table 2. Specific composition of the basic borosilicate glass powder used in Example 1.
[0048] Mass fraction (wt%) 54.73 14.96 5.34 2.66 4.51 8.20 5.33 4.27
[0049] 2. Mix all the powder samples weighed above in an agate mortar for 45 minutes, then transfer them to a 100mL corundum crucible and place them in a high-temperature box-type resistance furnace.
[0050] 3. By controlling the heating program, the temperature is raised from room temperature to 800℃ at a rate of 10℃ / min and held for 2 hours, then raised to 1300℃ for melting for 3 hours, and then poured onto a preheated steel plate to cool and obtain a glass-cured sample.
[0051] Figure 1 The image shows the XRD pattern of the borosilicate glass cured body prepared in this embodiment. Figure 1 CL0 in the text refers to the glass-cured sample obtained when La2O3 was added at a mass percentage of 0 wt%. Figure 1 CL1 in the sample refers to the glass-cured sample obtained when La2O3 was added at a mass percentage of 1 wt%. Figure 1 The CL2 in the sample refers to the glass-cured sample obtained when La2O3 was added at a mass percentage of 2 wt%. Figure 1 The CL3 in the sample refers to the glass-cured sample obtained by adding La2O3 at a mass percentage of 3 wt%. Figure 1 CL4 in the sample refers to the glass-cured sample obtained by adding La2O3 at a mass percentage of 4 wt%. Figure 1 CL5 in the sample refers to the glass-cured sample obtained by adding La2O3 at a mass percentage of 5 wt%. Figure 1 CL6 in the sample refers to the glass-cured sample obtained by adding La2O3 at a mass percentage of 6 wt%. Figure 1It can be seen that the characteristic peak of CeO2 can be clearly observed in the CL0 sample, proving that when the mass percentage of La2O3 added is 0 wt%, the mass percentage of CeO2 in the glass-cured body is 15 wt%, which will cause CeO2 to precipitate from the glass-cured body. As the mass percentage of La2O3 added in the glass-cured body increases, it can be seen from the XRD characteristic peaks of the glass-cured body sample that the intensity of the characteristic peak of CeO2 in the glass-cured body sample decreases significantly until it disappears completely. This proves that the present invention effectively improves the capacity of borosilicate glass to contain CeO2 by adding La2O3, which is a component of high-level radioactive waste liquid and can also be used as an actinide analog nuclide, to the basic borosilicate glass and the simulated nuclide CeO2, thereby obtaining a glass-cured body with a larger capacity to contain CeO2.
[0052] Figure 2 The images shown are the scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS) spectra of the vitrified sample prepared in this embodiment. Figure 2 In the image, 'a' represents the scanning electron microscope (SEM) image of the CL0 sample. Figure 2 In the image, b is the scanning electron microscope (SEM) image of sample CL1. Figure 2 In the image, c represents the scanning electron microscope (SEM) image of the CL2 sample. Figure 2 In the image, d represents the scanning electron microscope (SEM) image of the CL3 sample. Figure 3 This is the energy dispersive spectroscopy (EDS) spectrum of the CL0 sample. Figure 2 It can be seen that when the mass percentage of CeO2 in the glass-cured body is 15 wt%, a large amount of CeO2 crystals precipitate in the CL0 sample. Adding 1 wt% La2O3 to the glass-cured body significantly reduces the amount of CeO2 precipitated. Further increasing the mass percentage of La2O3 to 2 wt% results in very little CeO2 precipitation. When the mass percentage of La2O3 reaches 3 wt%, no CeO2 precipitates at all. Figure 3 The presence of e further confirms that the crystalline phase precipitated in the CL0 sample is CeO2.
[0053] Chemical stability tests were conducted on the glass-cured samples prepared in the examples. The specific test method for the leaching test was the ASTM Product Conformity Test Method (PCT). The test results are shown in Table 3.
[0054] Table 3. Normalized leaching rates of Ca, Si, and Ce elements in the solidified samples prepared in Example 1 on day 28.
[0055]
[0056] As shown in Table 3, the chemical stability of the cured body obtained by this invention is also excellent. The introduction of La2O3 can also improve the chemical stability of the cured body. After 28 days, the normalized leaching rates of Ca and Si elements remain at 10%. -4 g·m -2 ·d -1 Ce element consists of 10 -7 g·m -2 ·d -1 As the concentration of La2O3 increases, the leaching rate decreases to an undetectable level, and the leaching rate of La element cannot be measured by instruments, demonstrating excellent anti-leaching performance.
[0057] Example 2
[0058] The preparation method is basically the same as that in Example 1, except that step 2 is replaced by mixing all powder samples in a planetary ball mill for 45 minutes, then transferring them to a 100 mL corundum crucible and placing them in a high-temperature box-type resistance furnace.
[0059] Example 3
[0060] The preparation method is basically the same as that in Example 1, except that step 3 is replaced by: controlling the heating program, heating from room temperature to 800°C at a rate of 5°C / min and holding for 2 hours, then heating to 1300°C and melting for 3 hours, and then pouring it onto a preheated steel plate and cooling to obtain a glass-cured sample.
[0061] Example 4
[0062] The preparation method is basically the same as that in Example 1, except that step 3 is replaced by: controlling the heating program, heating from room temperature to 850°C at a rate of 5°C / min and holding for 2 hours, then heating to 1300°C and melting for 3 hours, and then pouring it onto a preheated steel plate and cooling to obtain a glass-cured sample.
[0063] As can be seen from the above embodiments, the present invention adds La2O3, which is a component of high-level radioactive waste liquid and can also be used as an actinide analog nuclide, to the base glass and the simulated nuclide CeO2. After grinding and mixing in an agate mortar and pestle and firing at high temperature, a glass-cured body with a larger capacity for CeO2 is finally obtained.
[0064] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for increasing the inclusion capacity of CeO2 in borosilicate glass cured body, characterized in that, Includes the following steps: Borosilicate glass powder, CeO2, and La2O3 are mixed to obtain a mixture. The composition of the borosilicate glass powder is expressed in the form of oxides, with the following mass percentages: SiO2 54.73%, B2O3 14.96%, Na2O 5.34%, Li2O 2.66%, Al2O3 4.51%, CaO 8.20%, MgO 5.33%, and BaO 4.27%. Specifically, the mass percentage of CeO2 in the mixture is 15%, and the mass percentage of La2O3 in the mixture is 3-5%. The mixture is melted to obtain a glass melt; The glass melt is cooled to obtain a borosilicate glass solidified body.
2. The method according to claim 1, characterized in that, The mixing includes grinding, and the mixing time is 40-45 minutes.
3. The method according to claim 1, characterized in that, The melting and holding temperature is 1250~1300℃, and the holding time is 2~3h.
4. The method according to claim 3, characterized in that, The heating process from room temperature to the melting holding temperature includes: heating from room temperature to an intermediate temperature at a first heating rate, performing a pre-holding treatment at the intermediate temperature, and then heating from the intermediate temperature to the melting holding temperature at a second heating rate; the intermediate temperature is 800~850℃, and the pre-holding treatment time is 1~2h.
5. The method according to claim 4, characterized in that, The first heating rate and the second heating rate are independently 5~10℃ / min.
6. The method according to claim 1, characterized in that, After obtaining the glass melt, before cooling, the process further includes: casting the glass melt, wherein the mold used for casting is preheated.
Citation Information
Patent Citations
Method for curing and treating high-level waste by using glass powder
CN116002981A
Method for vitrifying radioactive rare earth waste
KR101507148B1